Deforestation Impacts on Orographic Precipitation in the Tropical Andes - Eghdami, Masih; Barros, Ana P. (Frontiers in Environmental Science, 2020)
This study examines the implications of Tropical Montane Forests (TMFs) loss on orographic precipitation in the Eastern slopes of the Andes (EADS). The focus is on moist processes for synoptic regimes associated with significant EADS precipitation: 1) monsoon rainfall for weak and strong South America Low-Level Jet (LLJ) conditions, and 2) heavy rainfall associated with cold air intrusions (CAI) in the dry season. High-resolution simulations using the Weather Research and Forecasting (WRF) model were conducted for realistic and modified land-cover resulting from the conversion of TMFs to savannah. The deforestation scenarios result in 50-100% decrease (up to 400 J kg-1) in Convective Available Potential Energy (CAPE) spatially organized by land-cover change along the EADS. Analysis of the differences in simulated frequency distributions of rainfall intensity show robust daytime increases in light rainfall (< 2 mm hr-1) and decreases in moderate rainfall rates (2-10 mm hr-1) in the altitudinal band 500-2,000 m where orographic enhancement is dominant. Whereas there are negligible changes in the spatial patterns of precipitation and hydrologic response for monsoon conditions, rainfall accumulations decrease for all cases, and the precipitation maxima shift downslope into the Amazon lowlands. Changes in rainfall amount and intensity result in runoff decreases of 5-10% at the event-scale for the CAI case. Sensitivity simulations for lower initial soil moisture conditions indicate a strong positive feedback of forest loss to hydrologic drought along the EADS foothills in the austral spring when CAIs play a key role in the tropical EADS dry season hydrometeorology.